Psychological features of the ability to arbitrary governing of a deviant personality - Сорока, Анатолій Володимирович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
Psychological features of the ability to arbitrary governing of a deviant personality. The article presents the results of studies of local governing ability of an arbitrary deviant individual in accordance with the performance of our proposed early system-complex [2; 5]. Using the «system of self-willed person» we identified and assessed performance using the procedure «The ability to self-management», developed by M. M. Peysahov which determines the levels of self-management ability formation in an individual from arbitrary (high, medium, low). Arbitrary self-rule is seen by us as a part of a self-willed personality. Taken together, the indicators of techniques subscales reveal the subject’s ability to control his behaviour in the aspect of the activity approach. Insufficient development of a component, with the cycle, has a negative impact on the next steps and the whole process of self-identity. We also identified features of the ability to arbitrarily selfgoverning in the different age groups studied after serving their sentence for optimization of the resocialization in the society